Improving Of Mother's Skill About Giving Early Sex Education By Audiovisiual Media (AVA) - Widia Ilmiah; Fifin Maulidatul Azizah (Jurnal Ilmiah Kesehatan, 2022)
Cases of sexual exploitation and pedophilia become the phenomenon of the iceberg. Child Protection Commission Data found 120 cases of sexual violence (2016) and 116 (2017), in East Java 393 (2017) and 117 (February 2018), in Probolinggo 35 cases (January-April 2016). The preliminary study that 16 mothers known 69% difficulty answering questions about their child's sexuality. Purpose to analyze improving mother’s skills about giving early sex education by AVA. Methods were pre-experimental pre-post-test design. The population was all mother, preschool children in Condong and Sumbersecang were 234 people, the sample was 146, simple random sampling, instrument questionnaires, observation sheet, video, Fisher's Exact Test. The results that 74.7% of mothers have 25-40 y.o (mean 32.1), 64.4% as housewives, 45.9% have an income of 500.000-1 million IDR. Fisher's Exact Test of age toward skills, employment toward skills, the family income toward skill (p1=0.000; p2=0.000; p3=0.000). Several 92.5% mothers have the low skill to give sex education before training; 76.7% of mothers have good skill after training (p = 0.048). The provision of sex education training with AVA can improve the mother’s skills. The mothers must have the skill to give early sex education to prevent child sex crimes.